2017
DOI: 10.1108/jpmh-07-2017-0027
|View full text |Cite
|
Sign up to set email alerts
|

GoodYarn: building mental health literacy in New Zealand’s rural workforce

Abstract: Purpose “GoodYarn” is a skills-based workshop that focusses on building mental health literacy in rural communities, members of which are known to experience geographic, attitudinal and service configuration barriers to accessing mental health services. The purpose of this paper is to evaluate the impact of the GoodYarn project on raising mental health literacy in the rural community. Design/methodology/approach GoodYarn is primarily for farmers, their families and farm workers, as well as the “farmer facing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…Evidence suggests that increasing mental health literacy can help to reduce mental health struggles within the general population [15]. Previous work in farming populations has indicated that tailoring MHL programs to farmers may result in the greatest impact for participants [10,11,16]. We evaluated the effectiveness of "In the Know", a mental health literacy training program that was developed in partnership with the Canadian agricultural community and partners from mental health, over a 6-month period.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Evidence suggests that increasing mental health literacy can help to reduce mental health struggles within the general population [15]. Previous work in farming populations has indicated that tailoring MHL programs to farmers may result in the greatest impact for participants [10,11,16]. We evaluated the effectiveness of "In the Know", a mental health literacy training program that was developed in partnership with the Canadian agricultural community and partners from mental health, over a 6-month period.…”
Section: Discussionmentioning
confidence: 99%
“…Our evaluation study builds on the formal evaluation of the MHL training that was tailored to the agricultural community in New Zealand (GoodYarn), which showed improvements in mental health awareness, confidence, and knowledge from pre-to post-training but indicated that future research would benefit from longer-term follow-ups [11]. The "In the Know" evaluation addressed this gap, assessing the impact of the training beyond the "immediate post-training timepoint" by including follow-up assessments at 3 and 6 months post-training.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7,11 Little is known about why some farming families are more vulnerable to mental health problems than others. 7 Solutions have primarily been centred around health promotion (mental well-being); recognising the signs and symptoms of suicide (mental health literacy) 12 ; as well as ensuring that mental health services are available and resourced to address the needs of these often isolated communities. The notion of the resilient farmer and resilient farming systems are currently the dominant discourses in addressing concerns about farmers' mental well-being as well as mental illness in New Zealand.…”
Section: Introductionmentioning
confidence: 99%